Crafting Cultural Connection: Human-Centred Design Approach for Promotional Product Design Development Inspired by Myths and Legends - Abu Ali; Siti Salwa Isa; Junita Shariza Mohd Nasir; Nor Lelawati Jamaludin; Wan Zaiyana Mohd Yusof; Siti Suriawati Isa (Wacana Seni Journal of Arts Discourse, 2025)
The study on Crafting Cultural Connections examines the complex interplay between design, culture, and people’s experiences in promotional product production. Inspired by Langkawi’s rich mythology, this research promotes a Human-Centred Design (HCD) approach and seeks to educate novice industrial designers on how to utilise the approach in developing products that create value for people. This study is driven by three critical challenges: (1) the underrepresentation of cultural heritage in promotional product design, (2) the disconnect between designers and end-users in integrating culturally inspired product design, and (3) the lack of awareness among locals and tourists about myths and legends due to the dominance of digital entertainment and shifting cultural preferences. This research begins with an extensive understanding of the context of culture and belief, user awareness, and experiences, which serve as the foundation for well-informed design decisions. It is followed by designers who hold collaborative workshop design development sessions with local stakeholders, including renowned storytellers and seasoned tourism experts, to ensure the product draws inspiration from Langkawi’s rich tapestry of stories and tales. They then modified prototypes based on user feedback to find a balance between visual aesthetics and functionality. Documenting and reflecting on this process motivates novice industrial designers to engage in hands-on learning by adopting the HCD approach in design development to produce innovative products. This research will highlight the physical outcomes of this journey, showcasing meticulously created products and assessing their impact on using the HCD approach to improve cultural awareness among users.